2017
DOI: 10.1177/1533317517728333
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Between Apathy and Depression in Patients With Parkinson Disease Dementia

Abstract: In Parkinson disease (PD), apathy and depression often overlap, making it difficult to differentiate between them. This study sought to analyze apathy and depression in patients with PD dementia (PDD). Forty patients were diagnosed with PDD using the Movement Disorder Society criteria. A statistically significant correlation was identified between worsening dementia and an improvement in depression ( r = .3695; r = .1365, 95% confidence interval [CI]: 0.0985 to 05.894, P = .0044) and between worsening dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…On the other hand, we found that depression correlated with apathy. Depression and apathy are the most frequent neuropsychiatric disorders in neurodegenerative diseases and their co‐occurrence is expected in many parkinsonian syndromes (Camargo et al., 2018 ; Santangelo et al., 2018 ) and dementias (Collins et al., 2020 ). Distinguishing apathy from depression can be a major challenge due to an overlap in symptom, despite many studies suggested that they are separate entities underlined by different neural networks (Isella et al., 2002 ; Kirsch‐Darrow et al., 2006 ; Mayberg, 1994 ; Pluck & Brown, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found that depression correlated with apathy. Depression and apathy are the most frequent neuropsychiatric disorders in neurodegenerative diseases and their co‐occurrence is expected in many parkinsonian syndromes (Camargo et al., 2018 ; Santangelo et al., 2018 ) and dementias (Collins et al., 2020 ). Distinguishing apathy from depression can be a major challenge due to an overlap in symptom, despite many studies suggested that they are separate entities underlined by different neural networks (Isella et al., 2002 ; Kirsch‐Darrow et al., 2006 ; Mayberg, 1994 ; Pluck & Brown, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…For numerous somatic diseases, an association with depression is well-established. For example, patients with multiple sclerosis (8), stroke (9), parkinson's disease (10), diabetes mellitus (11), breast cancer (12) or heart failure (13) have an elevated risk for developing a major depressive disorder (MDD). From a psychiatric perspective, it is important to note that a recently published study with 1,237,194 participants showed that individuals who exercised (various types of disciplines) had 1.49 (43.2%) fewer days of poor mental health in the past month than non-exercising individuals (14).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging literature has shown a relationship between psychological symptoms like depression and risk of neurodegenerative disorders including dementia ( Bennett & Thomas, 2014 ; Landes, Sperry, Strauss, & Geldmacher, 2001 ; Nagayama et al, 2016 ; Oguru, Tachibana, Toda, Okuda, & Oka, 2010 ). Recent investigations highlight apathy as a separate entity from depression ( Marin, Fogel, Hawkins, Duffy, & Krupp, 1995 ; Starkstein, Petracca, Chemerinski, & Kremer, 2001 ), which has been uniquely associated with cognitive and functional decline in neurologic diseases ( Camargo, Serpa, Jobbins, Berbetz, & Sabatini, 2018 ; Palmer et al, 2010 ; Vicini Chilovi et al, 2009 ). Apathy predicts worse functional and cognitive outcomes after a stroke and in Parkinson’s disease (PD) ( Caeiro, Ferro, & Costa, 2013 ; Cohen, Aita, Mari, & Brandt, 2015 ; Hama et al, 2007 ).…”
mentioning
confidence: 99%